Street Pastors in the Night-Time Economy: harmless do-gooders or a manifestation of a New Right agenda?. Issue 1 (14th November 2018) - Johns, Nick; Green, Alison; Swann, Rachel; Sloan, Luke
Abstract : Purpose: The purpose of this paper, which follows an earlier paper published in this journal, is to explore the shape and nature of plural policing through the lens of New Right ideology. It aims to reinforce the understanding that policy is driven by both neoliberalism and neoconservatism, not simply the former. In policy terms, it uses the vehicle of a faith-based initiative – the Street Pastors – to consider how the strategic line of plural policing may be shifting. Design/methodology/approach: The research that informs this paper spans 2012 to the present day incorporating a multi-method evaluation, an ongoing observation with informal interviews, and two e-mail surveys directed at university students in Plymouth and Cardiff. In addition, the authors carried out a critical analysis of a research report produced by van Steden and a documentary analysis of national newspaper reports of Street Pastor activities. Findings: In a previous paper, the authors provided evidence to support the contention of Jones and Lister (2015) that there has been a shift in the landscape of plural policing. The Street Pastors initiative is a movement from "policing by the state" towards "policing from below". The authors suggest here that there may be evidence to speculate that another shift might occur from "policing from below" to "policing through the state". Ultimately, the authors contend, such shifts reflect and serve the dominance of New Right ideology in social and public policy. Research limitations/implications: The research limitations of this paper are twofold. First, the surveys had very small sample sizes and so the results should be treated with caution. The authors have underlined this in detail where necessary. Second, it is informed by a series of related though discrete research activities. However, the authors regard this as a strength also, as the findings are consistent across the range. The implications relate to the way in which policy designed to encourage partnership might lead to off-loading public responsibilities on the one hand, while allowing co-option on the other hand. Social implications: The practical implications are indivisible from the social implications in the authors' view. The neoliberal and neoconservative dimensions of the current dominant ideology are using local initiatives to save public money and reify disciplinary features of social and public policy. Originality/value: The originality of this research relates to the way it was conducted, drawing together the products of discrete but related activities. It adds to the growing research landscape involving the Street Pastors, an important faith-based, publicly backed initiative. But more importantly, it underlines how the two dimensions of New Right ideology come together in practice. The example of the Street Pastors indicates, through the lens of plural policing, how voluntary and local initiatives are being used to refocus the priorities of social and public policy.